Analysis of the Use of Jarimatics Learning Method in Multiplication Material for Grade 3 Fatmawati Elementary School UPI Laboratory Campus in Cibiru - Siti Fadia Nurul Fitri; Dede Margo Irianto (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This study aims to analyze the effectiveness of the jarimatika method in improving the ability to solve mathematical problems in elementary school students. The Jarimatics method is a mathematical approach that uses the basic principles of addition, subtraction, multiplication and division to solve mathematical problems in a way that is more intuitive and easily understood by students. This research was conducted by means of a literature review. The data collection technique used in this study was to use research results obtained from various journals, then further analyzed by researchers. So that it can be found the effectiveness of using the jarimatic method in learning mathematics. The results of this study indicate that the Jarimatika method also provides an interesting and fun alternative in learning mathematics, which can motivate students who are less interested in mathematics to be more active and involved in the learning process.